2018
DOI: 10.1007/s10534-018-0130-6
|View full text |Cite
|
Sign up to set email alerts
|

Ferrous and ferric differentially deteriorate proliferation and differentiation of osteoblast-like UMR-106 cells

Abstract: The association between iron overload and osteoporosis has been found in many diseases, such as hemochromatosis, β-thalassemia and sickle cell anemia with multiple blood transfusion. One of the contributing factors is iron toxicity to osteoblasts. Some studies showed the negative effects of iron on osteoblasts; however, the effects of two biological available iron species, i.e., ferric and ferrous, on osteoblasts are elusive. Since most intracellular ionized iron is ferric, osteoblasts was hypothesized to be m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 36 publications
3
18
0
Order By: Relevance
“…With decreased osteoblast activity, calcium deposition decreases as well ( Figure 3 a) [ 30 , 35 , 36 ]. Several studies also indicate that serum iron will induce cleaved caspase 3 and caspase 7 of osteoblasts, inducing cell apoptosis [ 37 ]. Furthermore, oxidative stress (e.g., H 2 O 2 , ROS) produced by iron can inhibit osteoblast activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With decreased osteoblast activity, calcium deposition decreases as well ( Figure 3 a) [ 30 , 35 , 36 ]. Several studies also indicate that serum iron will induce cleaved caspase 3 and caspase 7 of osteoblasts, inducing cell apoptosis [ 37 ]. Furthermore, oxidative stress (e.g., H 2 O 2 , ROS) produced by iron can inhibit osteoblast activity.…”
Section: Discussionmentioning
confidence: 99%
“…The crucial transcription pathways for osteoblastogenesis, including RUNX2, Wnt-βcatenin, and ERK, are regulated by oxidative stress [ 39 ]. In one dose-dependent manner in vitro study, ferric (III) iron and ferrous (II) iron both decreased osteoblast cell survival rate, but osteoblast was more sensitive to ferric (III) than ferrous (II) [ 37 ]. However, many studies have pointed out that iron promotes osteoclast differentiation, activation, and bone resorption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iron overload-associated osteopenia and bone fracture are found in several diseases, such as thalassemia, which is an inherited anemia disease caused by underproduction of globin proteins [ 5 7 , 33 ]. Previous study suggested that extracellular iron inhibited osteoblast cell survival and induced osteoblast cell death [ 2 , 4 , 34 , 35 ]. In addition to the direct deleterious effects of iron on bone cells and bone remodeling process, intestinal calcium malabsorption has also been reported in thalassemia [ 1 , 8 , 9 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…While normal serum iron levels have been reported to be 10–30 μM, the concentration over 50 μM was detected in iron overload patients [ 36 , 37 ]. Therefore, FAC in a range of 100–200 μM was used to represent iron overload condition in previous studies [ 2 , 4 ]. The normal extracellular calcium levels are within the range of 2.1–2.6 mM [ 38 ].…”
Section: Discussionmentioning
confidence: 99%